Deployment of Augmented Reality Across Science Topics in Junior High School: A Review - Annisa Noviani; Norma Eralita (Jurnal Pijar MIPA, 2026)
The practical application of science education often encounters various challenges, particularly in conveying abstract scientific concepts in a tangible and meaningful manner for students. Many concepts in junior high school science, such as astronomical phenomena, biological structures, and environmental systems, are inherently abstract and difficult to visualize through conventional instructional approaches. Augmented Reality (AR) offers opportunities to integrate virtual and real environments, enabling abstract scientific concepts to be represented in interactive, visual forms that may support conceptual understanding and student engagement. This study aims to describe and explain patterns of Augmented Reality (AR) utilization across science topics in junior high school education in Indonesia. A Systematic Literature Review (SLR) was conducted following the PRISMA protocol to ensure transparency and rigor in the review process. A comprehensive literature search was conducted across Google Scholar, Scopus, and ERIC databases. Of the 874 articles identified, 17 studies met the predetermined inclusion criteria and were selected for data synthesis. The findings indicate that research on AR-based learning media at the junior high school level in Indonesia remains relatively limited, with much of it focused on specific science topics. The structure and function of living organisms and the solar system were the most covered topics, with 4 articles (31%) and 3 articles (23%), respectively, while other topics each had 1 article (7.7%). In contrast, earth and environmental science topics, including ecology and biodiversity, receive comparatively less attention. This review is limited to open-access studies conducted in Indonesia between 2016 and 2025 and focuses exclusively on junior high school science education. The results of this study provide an overview of current research tendencies and may serve as a reference for future studies seeking to examine AR implementation more comprehensively.